2006
DOI: 10.1254/jphs.fp0051085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subchronic Treatment With Selegiline on L-DOPA-Induced Increase in Extracellular Dopamine Level in Rat Striatum

Abstract: Abstract. Selegiline is used an adjunct to L-DOPA therapy. We investigated extracellular striatal dopamine (DA) level in awake rats treated with L-DOPA and/ or selegiline using a microdialysis method. Rats given 10 mg / kg, i.p. per day selegiline for 7 days were administered with a single dose of 100 mg / kg, i.p. L-DOPA 0 (3 h), 1, 3, 7, 14, 21, or 28 days after the last selegiline treatment. Carbidopa was administered 0.5 h before L-DOPA administration. The significant increase in basal DA level before L-DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…These results are in agreement with findings of ourselves and other studies showing that MAO-A is the major enzyme responsible for DA oxidative breakdown in both normal and 6-OHDA-lesioned striatum (Finberg et al, 1995;Lamensdorf et al, 1996;Wachtel and Abercrombie, 1994). It should be noted, however, that Adachi (Adachi et al, 2006) observed a reduction in [DA ec ] levels following L-dopa treatment in rats treated subchronically with selegiline, and attributed this effect to presynaptic inhibitory activation.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with findings of ourselves and other studies showing that MAO-A is the major enzyme responsible for DA oxidative breakdown in both normal and 6-OHDA-lesioned striatum (Finberg et al, 1995;Lamensdorf et al, 1996;Wachtel and Abercrombie, 1994). It should be noted, however, that Adachi (Adachi et al, 2006) observed a reduction in [DA ec ] levels following L-dopa treatment in rats treated subchronically with selegiline, and attributed this effect to presynaptic inhibitory activation.…”
Section: Discussionsupporting
confidence: 93%
“…Clearance of neurotransmitters from the extracellular space is executed by reuptake, enzymatic degradation, and dilution by diffusion (Garris and Wightman, 1995). Adachi et al (2006) demonstrated that a monoamine oxidase B inhibitor increased levels of L-DOPAderived DA in the DA-denervated striatum, indicating the involvement of the enzymatic degradation. A recent study suggests that diffusion mechanisms in the clearance of monoamines should not be ignored (Cragg et al, 2001).…”
Section: Introductionmentioning
confidence: 99%